The Study of Slow Bend Test and Hardness Test for Welded Rail Joints in Between Alumino Thermic and Flash Butt in Electrified Double Track Project (EDTP) Gemas-JB - Juki, Nur Hanisah; Mahyeddin, Mohd Eizzuddin (Progress in Engineering Application and Technology, 2022)
The Gemas - Jb EDTP project uses the welding method to connect the rail, which is a total of 197km/h with an allocation of RM7.5B from the government. Most Malaysian railway projects now use two types of welding, ATW and FBW, which both have the same purpose but vastly different mechanisms. The purpose of writing this study is to identify why most railway projects in Malaysia now need to use two kinds of rail connection welding. Result of this study FBW is much better than ATW in terms of quality, and time consuming but ATW has some advantages that FBW cannot afford. Both methods are important for the completion of any railway project in Malaysia today.